Co-morbid mental disability among Chinese elderly with motor disability: Based on a nationwide survey - Guo, Chao (PLoS One, 2018)
This study aimed to investigate the prevalence rate and associated factors of co-morbid mental disability among the elderly with motor disability. Data was obtained from the second China National Sample Survey on Disability (CNSSD). 250,752 older adults aged 65 years and above were sampled from 5964 sites, 2980 towns, 734 counties in 31 provinces in China. Descriptive statistics were used for population-weighted numbers and prevalence of co-morbid mental disability by different characteristics. Univariate logistic regression and multivariate logistic regression were used to calculate the association between mental disability, and the factors of co-morbid mental disability among physical disability. Among the elderly with motor disability, 275,607 persons (2.28%, 99% CI: 1.97–2.59) had co-morbid mental disability at the survey time, which was significantly higher than those without motor disability (OR: 2.11, 99% CI: 1.83–2.43). The factors associated with a higher risk of co-morbid mental disability included urban areas (OR: 1.38; 99% CI: 1.04–1.84), east (2.60, 1.76–3.83) or west (1.65, 1.06–2.55) regions, having other co-morbid disabilities (5.93, 4.48–7.85), and having more severe motor disability (Moderate: 1.81, 1.28–2.57; Severe: 2.90, 2.08–4.04; Extremely severe: 4.22, 2.96–6.01). The elderly with motor disability have a high risk of co-morbid mental disability, especially for higher socioeconomic groups. These findings highlight the need of and will be beneficial for implementing more comprehensive prevention and rehabilitation strategies, to prevent and control the emergence and development of multiple disabilities and promote the physical and mental health of the elderly.